Quantifying the Release of Biomarkers of Myocardial Necrosis from Cardiac Myocytes and Intact Myocardium. (6th January 2020) - Marjot, Jack; Kaier, Thomas E; Martin, Eva D; Reji, Shiney S; Copeland, O'Neal; Iqbal, Mohammed; Goodson, Bob; Hamren, Sarah; Harding, Sian E; Marber, Michael S
Abstract: BACKGROUND: Myocardial infarction is diagnosed when biomarkers of cardiac necrosis exceed the 99th centile, although guidelines advocate even lower concentrations for early rule-out. We examined how many myocytes and how much myocardium these concentrations represent. We also examined if dietary troponin can confound the rule-out algorithm. METHODS: Individual rat cardiac myocytes, rat myocardium, ovine myocardium, or human myocardium were spiked into 400-μL aliquots of human serum. Blood was drawn from a volunteer after ingestion of ovine myocardium. High-sensitivity assays were used to measure cardiac troponin T (cTnT; Roche, Elecsys), cTnI (Abbott, Architect), and cardiac myosin-binding protein C (cMyC; EMD Millipore, Erenna ® ). RESULTS: The cMyC assay could only detect the human protein. For each rat cardiac myocyte added to 400 μL of human serum, cTnT and cTnI increased by 19.0 ng/L (95% CI, 16.8–21.2) and 18.9 ng/L (95% CI, 14.7–23.1), respectively. Under identical conditions cTnT, cTnI, and cMyC increased by 3.9 ng/L (95% CI, 3.6–4.3), 4.3 ng/L (95% CI, 3.8–4.7), and 41.0 ng/L (95% CI, 38.0–44.0) per μg of human myocardium. There was no detectable change in cTnI or cTnT concentration after ingestion of sufficient ovine myocardium to increase cTnT and cTnI to approximately 1 × 10 8 times their lower limits of quantification. CONCLUSIONS: Based on pragmatic assumptions regarding cTn and cMyC release efficiency, circulating species, and volume of distribution, 99th centile concentrations may be exceeded by necrosis of 40 mg of myocardium. This volume is much too small to detect by noninvasive imaging.